Correlational Study Between Applied Science and Knowledge Management: Description of Conceptual Framework - Siew Poh Phung, Dr.; Valliappan Raju, Assoc. Prof. Dr.; Imran, Dr. (International Journal of Engineering and Technology, 2019)
In applied science, one of the critical components involves knowledge management. Most of the information accruing from science-related areas tends to be grounded and distributed in platforms such as articles, course books, and research reports. Given the information corpus, it tends to be scattered and conflicting. Motivated by the need to address this adversity, the current paper examines knowledge management system (KSM) provisions. The paper targets the context of a learning server interacting with the respective data sources, paving room for various access forms to a common server. To ensure that various clientsâ€™ diverse needs are satisfied, the learning server offers diverse customer frameworks. Some of the issues that arise include preparation, instruction, clarification, counsel, and anticipation. For the server, a central role involves research and analysis through writing audit and speculation testing.Â